2008
DOI: 10.5194/aab-51-389-2008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of heat stress and age on the percentage of calcium carbonate in eggshell and the percentage of broken and cracked eggs

Abstract: Influence of heat stress and age on the percentage of calcium carbonate in eggshell and the percentage of broken and cracked eggs AbstractThe influences on eggs of high temperatures and age were examined in hens that were from a poultry farm situated in the south of the Republic of Macedonia where the average summer temperatures were always the highest. The experiment lasted for 9 months and comprised a period of three seasons: summer, autumn and winter. Maximum and minimum temperatures and relative humidity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
3
3
0
Order By: Relevance
“…Similarly, specific gravity was lower at the higher temperature, which is in agreement with Mashaly et al (2004) and Franco-Jimenez et al (2007), who described lower values of specific gravity in birds under heat stress and explain this situation due to lower plasma calcium as a result of reduced feed consumption and lack of minerals for eggshell formation. This assumption corresponds with findings of Nikolova et al (2008), who stated that in eggs produced under heat stress, calcium carbonate percentage was lower. On the other hand, Cusack et al (2003) gave the reason for thinner eggs at higher temperatures as the more rapid precipitation of calcium carbonate.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, specific gravity was lower at the higher temperature, which is in agreement with Mashaly et al (2004) and Franco-Jimenez et al (2007), who described lower values of specific gravity in birds under heat stress and explain this situation due to lower plasma calcium as a result of reduced feed consumption and lack of minerals for eggshell formation. This assumption corresponds with findings of Nikolova et al (2008), who stated that in eggs produced under heat stress, calcium carbonate percentage was lower. On the other hand, Cusack et al (2003) gave the reason for thinner eggs at higher temperatures as the more rapid precipitation of calcium carbonate.…”
Section: Discussionsupporting
confidence: 92%
“…Incidence of egg cracks and mortality was significantly higher in summer season. The same results had been shown in experiment by Nikolova et al (2008) Season has no significant effect (P > 0.05) on eggshell thickness was concluded by Haque et al (2006). This result is dissimilar to the findings of Izat et al (1985) and Wilheim (1940).…”
Section: Resultssupporting
confidence: 85%
“…Incidence of egg cracks and mortality was significantly higher in summer season. The same results had been shown in experiment by Nikolova et al (2008).…”
Section: T a B L Esupporting
confidence: 88%
“…Significant variations in egg weight were noticed by many researchers (Monira et al, 2003;Аnderson et al, 2004). Nikolova and Kocevski (2004), Nikolova et al (2008) and later Kocevski et al (2011) reported differences in egg weight and quality (strenght) of egg shell due to genotypes and also as influenced by season (high summer temperature).…”
Section: Introductionmentioning
confidence: 98%